Upregulation of NKX2.2, a target of EWSR1/FLI1 fusion transcript, in primary renal Ewing sarcoma - Yamamoto, Yoshinari (J Cytol, 2015)
Renal Ewing sarcoma (ES) is a rare malignant tumor characterized by fusion of the EWSR1 gene with a member of the ETS family of oncogenes, arising at a specific chromosomal translocation. Diagnosis of ES can be problematic, especially from cytological or small bioptical specimens because the differential diagnoses comprising a diverse group of small round blue cell tumors (SRBCTs). We report a case of primary renal ES in a young male, which had a t(11;22) (q24;q12) chromosome translocation encoding a type2 EWSR1/FLI1 fusion transcript. The tumor cells showed diffuse cytoplasmic immunoreactivity for CD99 and diffuse nuclear immunoreactivity for NKX2.2, an important oncogenic transcriptional target of EWSR1/FLI1, not only in the histological, but also in the cytological specimens. From the results of this case, we speculate that NKX2.2, in combination with CD99, may be a useful immunocytochemical marker to distinguish renal ES from other SRBCTs of kidney.